Epiphany in Waiting - Rajabali, Anar (Journal of the Canadian Association for Curriculum Studies, 2018)
Rumi writes “Keep walking, though there’s no place to get to. Don’t try to see through the distances . . . move within” (Barks, 1997, p. 278). In this lyrical essay, I begin by enacting a walk I took with my mother along the ocean. I poetically dwell in a sensual phenomenological inquiry where I attune to the experience of this walk as it is unfolding: the images, the colours, the gestures, the scents, the sounds and the silences. Through the (re)telling of this pivotal event, I am then transported to the past, where I (re)enter a painful moment in a classroom. As in the line of the altering hues of the horizon that we walk alongside of, I relinquish to this line of inquiry. As I theorize this space in between the present and the past, I am brought to an epiphany and transcend both experiences into a renewed understanding of my pedagogical self. Here, I learn how the body holds the words; and in poetry as a physical, emotional, and spiritual walking through, I then enter into a place of light. The keen lessons of an encountering give in healing and meaning, illuminating the future with promise and with purpose.